Effect of salinity acclimatisation and administration of hormones on oocyte maturation, ovulation and spawning of goldspot mullet Liza parsia (Hamilton, 1822) reared in brackishwater pond - Kumar, Prem; Biswas, G.; Ghoshal, T.K.; Christina, L.; Behera, P.; Kailasam, M. (Indian Journal of Fisheries, 2020)
Two separate experiments were conducted to evaluate the effect of salinity acclimatisation and administration of hormones on oocyte growth of Liza parsia (Hamilton, 1822). In the first experiment, broodstock fishes in the sex ratio of 2:1 (male:female) were acclimatised toÂ  30 ppt salinity (which is the desired salinity for breeding L. parsia) in 24, 48 and 72 h of duration (n=6). Oocyte diameter from the experimental fishes were measured before and after salinity acclimatisation. The results showed that the acclimatisation to breeding salinity reduced oocyte diameter (p